Challenges in the classification of fibrotic ILD: Patient case 2 - Wijsenbeek, Marlies (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Patient presentation and diagnostic work-up The patient is a 72-year-old man presenting with dyspnoea on exertion. He is a former heavy smoker (40 pack-years) and his father, now deceased, had rheumatoid arthritis (RA). On physical examination he had mild bi-basilar crackles but no finger clubbing. Autoimmune serology was positive for rheumatoid factor (RF: 25 IU/ml). Lung function tests showed normal FVC, a FEV1/FVC ratio of 72% and a TLCO of 49% predicted. Lung CT showed centrilobular and paraseptal emphysema, subpleural fine reticulation and traction bronchiolectasis, with no clear basal predominance (Figure 1). BAL cytology showed 83% alveolar macrophages, 12% lymphocytes, 3% neutrophils, and 2% eosinophils. [...]